Educational Values in the Saman Dance in Blangkejeren Gayo Lues - Asma, Masyitah Ultari; Triyanto, Triyanto Triyanto; Hartono, Hartono Hartono (Universitas Negeri Semarang, 2019)
Saman dance is a traditional dance of the Gayo community which developed in Blangkejeren Gayo Lues danced by men. Saman dance was originally used as a means of propaganda media in the spread of Islam. In Saman dance there are many educational values ​​that are beneficial to the community. This study aims to examine the educational values ​​of Saman dance performance. The research was located in Blangkejeren Gayo lues, Aceh Province. Data collection techniques are observation, interviews, and documentation. Data validation techniques used triangulation. Data analysis techniques used descriptive analysis. The results of this study are that the Saman Dance has educational values, namely the religious values ​​found in poetry, movements and clothing used by Saman dancers. The value of friendship lies in the enthusiasm of the audience and the dancers who are made as a unifier of the Gayo community, the value of tolerance can also be seen in the poems sung by the Penangkat. The togetherness value in the saman dance is clearly seen in the cohesiveness among dancers and in the variety of movements being danced, and the value of confidence is seen in the movements danced heroically by dancers.